2019
DOI: 10.1111/jonm.12827
|View full text |Cite
|
Sign up to set email alerts
|

Care delivery models: Challenge to change

Abstract: Aim The purpose of this project was to evaluate a partnership model of care delivery on nurse and patient satisfaction and clinical outcomes. Background Care delivery models result in practical staff assignment decisions based on perceived fairness. The division of labour lies in social interaction of participants. Research notes that partnership team models require effective communication skills and delegation abilities to sustain. Method This project used multiple methods in two study sites. A convenience sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Fernandez et al, ( 2012 ) reported that the evidence surrounding team nursing had inconsistent findings on falls and medication errors compared with other care models. On the contrary, several studies reported negative outcomes with team nursing such as increased adverse events compared with the patient allocation model (Havaei, MacPhee, & Dahinten, 2019 ), decreased mobility compared with a modified primary nursing model (Winslow et al, 2019 ), and decreased quality of care compared with primary nursing (Betz, Dickerson, & Wyatt, 1980 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fernandez et al, ( 2012 ) reported that the evidence surrounding team nursing had inconsistent findings on falls and medication errors compared with other care models. On the contrary, several studies reported negative outcomes with team nursing such as increased adverse events compared with the patient allocation model (Havaei, MacPhee, & Dahinten, 2019 ), decreased mobility compared with a modified primary nursing model (Winslow et al, 2019 ), and decreased quality of care compared with primary nursing (Betz, Dickerson, & Wyatt, 1980 ).…”
Section: Resultsmentioning
confidence: 99%
“…Findings across these studies were inconsistent. Three studies reported an improvement in job satisfaction (Dickerson & Latina, 2017 ; Downs & Hoil, 2004 ; Murphy, Pearlman, Rea, & Papzian‐Boyce, 1994 ); three studies reported a reduction (Hayman, Wilkes, & Cioffi, 2008 ; Mäkinen, Kivimäki, Elovainio, Virtanen, & Bond, 2003 ; Ryan, Poster, Auger, Davis, & Ringdahl, 1988 ); and three studies reported no difference (Carlsen & Malley, 1981 ; King, Long, & Lisy, 2015 ; Winslow et al, 2019 ). The systematic review by Fernandez et al, ( 2012 ) also found conflicting evidence about RN satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the development, implementation, and evaluation of an NCDM, focusing on the role of nursing [ 16 ] in terms of development strategies [ 17 ] and system evaluation control is crucial [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…11,23 One paper examined a Comprehensive Care Model of Nursing Care delivery in Korea. 24 The three remaining papers examined the introduction of a Modified TPC Model, 25 the introduction of a Partnership Care Delivery Model, 26 and another examined a collaborative model of care with RNs and LPNs. 27 The third systematic review examined usual care provided in a medical-surgical unit for geriatric clients when compared with a Geriatrics Unit ACE model of care.…”
Section: Nursing Care Delivery Modelsmentioning
confidence: 99%